2020
DOI: 10.3390/membranes10080165
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Electrochemical Characteristics of CJMCED Homogeneous Cation Exchange Membranes in Sodium Chloride, Calcium Chloride, and Sodium Sulfate Solutions

Abstract: Recently developed and produced by Hefei Chemjoy Polymer Material Co. Ltd., homogeneous CJMC-3 and CJMC-5 cation-exchange membranes (CJMCED) are characterized. The membrane conductivity in NaCl, Na2SO4, and CaCl2 solutions, permeability in respect to the NaCl and CaCl2 diffusion, transport numbers, current–voltage curves (CVC), and the difference in the pH (ΔpH) of the NaCl solution at the desalination compartment output and input are examined for these membranes in comparison with a well-studied commercial Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 97 publications
(155 reference statements)
2
24
0
Order By: Relevance
“…It can be seen that for heterogeneous Ralex membranes, the value of the f2 parameter is comparable to the value of this parameter for homogeneous membranes. Such values of this parameter were obtained in other works [34][35][36]. In [34], the authors suggested that such a value of the fraction of the intergel solution for these membranes is a consequence of the fact that the particles of the ion exchanger in these membranes are small enough and, at the same time, there are no macroscopic cavities inside the membrane that electrically neutral solutions can occupy.…”
Section: Conductivity Measurement Resultssupporting
confidence: 61%
“…It can be seen that for heterogeneous Ralex membranes, the value of the f2 parameter is comparable to the value of this parameter for homogeneous membranes. Such values of this parameter were obtained in other works [34][35][36]. In [34], the authors suggested that such a value of the fraction of the intergel solution for these membranes is a consequence of the fact that the particles of the ion exchanger in these membranes are small enough and, at the same time, there are no macroscopic cavities inside the membrane that electrically neutral solutions can occupy.…”
Section: Conductivity Measurement Resultssupporting
confidence: 61%
“…It can be seen that for heterogeneous Ralex membranes, the value of the 2 parameter is comparable to the value of this parameter for homogeneous membranes. Such values of this parameter were obtained in other works [24][25][26]. In [24], the authors suggested that such a value of the fraction of the intergel solution for these membranes is a consequence of the fact that the particles of the ion exchanger in these membranes are small enough and, at the same time, there are no macroscopic cavities inside the membrane, which electrically neutral solutions can occupy.…”
Section: Conductivity Measurementssupporting
confidence: 62%
“…The sorption of anthocyanins by the volume of CJMA-6 follows the same mechanism as in the case of i = 0. In addition, it is possible that a certain amount of Ant + in the composition of negatively charged colloidal particles penetrates into the pores of the CJMA-6 membrane [55], which are larger compared to the pores of CJMC-5 [49].…”
Section: The Mechanism Of Membrane Fouling By Components Of Model Sol...mentioning
confidence: 99%
“…), which are increasingly used in ED, including for the extraction of tartrates and deacidification of juices [2,16,43]. The study of the fouling of such membranes during the ED processing of juices and wines is at an early stage [43,49,50]. In addition, when studying the consequences of fouling, attention is mainly paid to the ion-exchange capacity, conductivity as well as the diffusion permeability of membranes [42,51,52] and, to a lesser extent, the behavior of ion-exchange membranes in an electric field [53].…”
Section: Introductionmentioning
confidence: 99%